Perfect risotto - Zavan, Laura (Les petits plats français, 2011)
A stylish guide to preparing the perfect risotto every time, you'll find basic information and easy-to-follow instructions, along with recipes for risottos with a range of flavorings: fruits and vegetables, fish and shellfish, and meat. Includes a conversion chart.